"Simple Taoism: a guide to living in balance / by C. Alexander Simpkins, and Annellen Simpkins" - "Simpkins, C. Alexander" (Dublin, 1999)
Simple instructions for exercises to lead a fuller life - meditation, breathing, chi kung and tai chi chuan. An informative discussion of the key Taoist concepts, including wu-wei (non-action), yin and yang, and Te (power, virtue, life). Other books by Annellen Simpkins Simple Zen.
Keywords: Taoism